PHYSICO-CHEMICAL PARAMETERS ASSESSTMENT OF CHILAR DAM WATER IN DIFFERENT SITES OF SHAJAPUR TOWN, M.P., INDIA - Kumar, BodaneArun (International Journal of Research -GRANTHAALAYAH, 2015)
The present investigation revealsthe quality of Dam water for public consumption to determine the Dam water of Shajapur town. Physico-chemical parameters of Dam water were monitored during the study period. The parameters investigated were pH, TDS, Alkalinity, Total Hardness, Chlorides, Magnesium, Fluoride, Nitrates, Dissolve Oxygen and COD. Results obtained from the study revealed that quality of Dam water during study season is well within the permissible limit and the Dam water is safe for drinking or fit for human consumption.